Los morteros “bilingües” del Valle del Ebro (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper deals with a new interpretation of ³bilingual´  stamps  on some mortars which were produced at the beginning of the Ist century BC in the mid Ebro valley imitating the shape of Emporiae 36,2 mortars. According to epigraphic Italic parallels, these bilingual stamps are understood as complementary texts refering to a commercial partnership among Italian and Iberian producers by means of slaves (officinatores) who are in charge of the workshops, that is exercere negotiationes per servos, a wellknown model in the Roman world during the Late Republic.